PERAN SKEMA OPSEN PAJAK (PIGGYBACK TAX SYSTEM) DALAM PENGUATAN DESENTRALISASI FISKAL - Rosewika, Danandjaja; Maharani, Agnesya; Putri, Nayya Sheptia (Politeknik Keuangan Negara STAN, 2025)
The implementation of fiscal decentralization in Indonesia has still not been optimal since the enactment of UU 25/1999 which only became formally effective in 2001. Therefore, the government needs to optimize fiscal decentralization which is now proposed in UU 1/2022 (UU HKPD), namely the implementation of a tax opportunity scheme (piggyback tax system). This research aims to describe how the tax opportunity scheme plays a role in strengthening regional financial capacity and compare it with the existing scheme in UU 28/2009 (UU PDRD). This research uses normative juridical methods through literature study and data analysis using comparative studies. This research concludes that the tax opportunity scheme increases regional independence and accelerates district/city revenues which have previously been received from the province in the form of periodic profit sharing, into direct transfers to each Regional General Cash Account. The implementation of the opportunity scheme relatively does not increase the burden on taxpayers. This opsen scheme eliminates the gap in collection between the provincial government and the distribution of revenue sharing from the province to the districts/cities.